Strategic Management Teacher Performance Development to Improve Learning Quality - Abdu Syahid; Iim Wasliman; Hendi Suhendraya Muchtar; Nanang Hanafiah (International Journal of Nusantara Islam, 2019)
Strategy Management for Teacher Performance Development to Improve the Quality of Lessons is a response to the quality of learning that still needs to be improved, by developing teacher performance, is a solution to improving the quality of learning. Focus of the problem: How to Implement Strategic Management of Teacher Performance Development to Improve the Quality of Learning. Specific objectives of this study are to identify and analyze: (1) Internal and External Environments, (2) Formulation of Strategy Formulation, (3) Strategy Implementation, (4) Teacher Performance Monitoring and Evaluation Management, (5) Strategic Steps to Overcome Problems and Weaknesses. Research methods and procedures refer to the qualitative research approach. The theories that underlie this research are strategic management theory, performance coaching theory, higher order thinking learning theory and madrasah culture theory. The main findings of this study are: (1) The principal of madrasah has not analyzed and combined strengths, weaknesses, opportunities and challenges into a strategic assumption conclusion that can be used as a basis for further strategic planning, (2) Strategy formulation is not based on strategic assumptions that maximize strength factors and minimizing the weakness factor by taking advantage of opportunities in facing challenges.